PERANCANGAN PROGRAM APLIKASI TES BUTA WARNA BERBASIS ANDROID - Tedi Budiman (INTERNAL (Information System Journal), 2019)
Color blindness test is one way to find out whether a person has color blindness or not, is usually done with the Ishihara method. This Ishihara method is a method where when running a test with this method, the patient is usually faced with a book containing a circle pattern (disk) with many points of various colors and sizes in it. The circle pattern is usually 14, 24 and 38 dishes. Tests like this are usually done in health agencies, one of which is the Cahaya Insani Clinic in Garut, West Java. The process of implementing a color-blind test is still done manually where people who want to do a color-blind test must come directly to the clinic, making people who did color-blind tests had to be willing to wait a long time to be able to do a color-blind test. In addition to these problems, the lack of knowledge and understanding of the community regarding color blindness, makes people less aware of the importance of color-blinding tests early on. Therefore, a media is needed that can do color blindness tests quickly and easily, coupled with information about color blindness that can provide insight to the community. Mobile based application Android is one of the right media to make it easy for people to obtain information. Starting from this, then made an Android-based color blindness test application to make it easier for people to do color blindness tests anytime and anywhere, and can used as a medium of information about color blindness.